Teologi Dalihan Natolu sebagai Simbol Persatuan dalam Adat Suku Batak Toba (Jurnal Pendidikan Agama dan Teologi, 2025)
The purpose of writing this article is to find out that Dalihan Natolu in Batak customs, especially us as Toba Batak people and we can understand that this theology is also connected to the concept of Dalihan Natolu as a symbol of unity in Toba Batak tribal customs and we also as Indonesian people are a reflection of traditions and culture that have been known throughout the world since the time of our ancestors. However, with the entry and domination of Western religions in Indonesia, traditional and cultural values ​​began to experience a process of desacralization and were even marginalized. As a result, the identity of the Indonesian people seems to be lost in expressing their beliefs. To face this challenge, a new theological model is needed that is rooted in what exists in Indonesia, in this case the concept of Dalihan Na Tolu, namely the customs of the Batak tribe. And dalihan na tolu is a kinship system that brings society to an egalitarian status in love and sacrifice.